Prolonged Exposure to Neonatal Hyperoxia Impairs Neuronal and Oligodendrocyte Maturation Associated with Long-Lasting Neuroinflammatory Responses in Juvenile Mice - Stefanie Obst; Meray Serdar; Karina Kempe; Dharmesh Hirani; Ursula Felderhoff-Müser; Josephine Herz; Miguel A. Alejandre Alcazar; Ivo Bendix (Cells)
Preterm infants often require oxygen supplementation, resulting in high risk for bronchopulmonary dysplasia (BPD) and neurodevelopmental deficits. Despite a growing number of studies, there is still little knowledge about brain injury in BPD models. Therefore, we exposed neonatal C57BL/6 mice to 85% oxygen from birth to postnatal day (P) 14. At P28, two weeks after recovery under normoxic conditions, right hemisphere was used for the analysis of mRNA and the left hemisphere for protein expression of neuronal cells, neuroinflammatory and vascularisation markers, analysed by real-time PCR and Western blot, respectively. Hyperoxia led to an altered expression of markers associated with neuronal and oligodendrocyte maturation and neuroinflammation such as Dcx, Nestin, Il-1β, Il-6, NG2, and YM1/2. These changes were accompanied by an increased expression of genes involved in angiogenesis and vascular remodelling, e.g., Vegf-a, Nrp-1, and Icam-1. Together, 14 days of hyperoxia triggered a phenotypic response, resembling signs of encephalopathy of prematurity (EoP).